2022
DOI: 10.1002/ehf2.14271
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of Growth differentiation factors 15 in Acute heart failure patients with preserved ejection fraction

Abstract: Aims There is an increasing proportion of hospitalized heart failure (HF) patients classified as HF with preserved ejection fraction (HFpEF) around the world. Growth differentiation factor 15 (GDF‐15) is a promising biomarker in HFpEF prognostication; however, the majority of the existing data has been derived from the research on undifferentiated HF, whereas the studies focusing on HFpEF are still limited. This study aimed to determine the prognostic power of GDF‐15 in the hospitalized patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It can regulate the process of inflammatory damage repair and the proliferation, differentiation, and remodeling of blood vessels through anti-oxidative stress and inflammatory responses [ 47 , 48 ]. Studies have shown that increased growth differentiation factor-15 level is an independent risk factor for cardiovascular events, all-cause death, HF readmission, and composite endpoints (all-cause death and first HFR) in patients with HFpEF, and its prognostic value may be better than NT-proBNP [ 49 - 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can regulate the process of inflammatory damage repair and the proliferation, differentiation, and remodeling of blood vessels through anti-oxidative stress and inflammatory responses [ 47 , 48 ]. Studies have shown that increased growth differentiation factor-15 level is an independent risk factor for cardiovascular events, all-cause death, HF readmission, and composite endpoints (all-cause death and first HFR) in patients with HFpEF, and its prognostic value may be better than NT-proBNP [ 49 - 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both are associated with incident HFpEF in population studies and are highly prognostic in patients hospitalized for HFpEF. 6,7 GDF-15 promotes weight loss, modulates macrophage phenotypes, and may represent a homeostatic response to inflammation; GDF-15 inhibition is not yet an obvious approach for HF prevention. In contrast, a large clinical trial (ZEUS [A Research Study to Look at How Ziltivekimab Works Compared to Placebo in People With Cardiovascular Disease, Chronic Kidney Disease, and Inflammation]: NCT05021835) is testing whether the monoclonal IL-6 antibody ziltivekimab reduces cardiovascular events (including, as a secondary end point, HF hospitalizations) in patients with CKD.…”
Section: Incident Hfpef and Hfref In Patients With Ckdmentioning
confidence: 99%
“…The paper by Jia et al . published in the current issue of ESC Heart Failure evaluates selected multifactorial algorithms predicting outcome in HFpEF 2 . After a literature search, the authors identified 16 studies testing 39 prognostic models for inclusion in the analysis.…”
Section: Figurementioning
confidence: 99%